Distribution and Population of Thomas's Langur (Presbytis thomasi, Collett 1892) in the Sikundur Research Station, Gunung Leuser National Park. - Ulfa Hansri Ar Rasyid; Syafruddin; Yunita Erma Wanda (JURNAL AGRIMENT, 2025)
Thomas's langur (Presbytis thomasi) is an endemic primate of northern Sumatra whose conservation status is increasingly threatened by habitat degradation. This study aims to assess the spatial distribution and population structure of P. thomasi within the Sikundur Research Station of Gunung Leuser National Park. Data collection was conducted using the concentration count method, including recording of GPS coordinates, elevation, group composition, sex ratio, and age classification. A total of 24 individuals were identified across six social groups in four research blocks (A–D), with adults comprising 70.83% of the observed population. The estimated population density was 4.8 individuals/km². Chi-square analysis (χ² = 22.50) indicated a significantly clumped distribution pattern. This pattern likely reflects ecological factors such as food tree availability, habitat structure, and social behavior. The findings highlight the importance of habitat quality and spatial connectivity for the conservation of this vulnerable species.